Survey on Urban Greenery Status in Residential Areas at the Center of Thu Dau Mot City, Binh Duong Province - Thi Thanh Thao, Nguyen; Thi Ngoc, Nguyen; Thi Thu Pha, Huynh (VNU Journal of Science: Earth and Environmental Sciences; Vol 41 No 2DO - 10.25073/2588-1094/vnuees.5225, 2025)
Greenery planning in residential areas is a critical task that must be undertaken when developing urban planning projects. Thu Dau Mot City, with its high housing density during a period of rapid urbanization, has seen a growing need for green spaces for recreation, exercise, health improvement, and relaxation, as well as the need for cool, shaded greenery. The study investigated the types and quantities of trees in two major residential areas, Chanh Nghia Residential Area and Hiep Thanh III Residential Area. The results systematized the tree species in both regions, showing compliance with state regulations. However, the quantity of trees remains relatively low according to Vietnam's standards. The study also surveyed residents' opinions in both residential areas and proposed several solutions for green space planning, aiming at improving the quality of life and the environment for the local population.